A new species of Haematobosca Bezzi (Diptera: Muscidae) from Thailand - Pont, Adrian C; Duvallet, Gérard; Changbunjong, Tanasak (Zootaxa, 2020)
A new species of biting-fly from northern Thailand is described as Haematobosca aberrans sp. nov. (Muscidae). It differs from all known species of Haematobosca by the absence of the anterior katepisternal seta.